Icon - Freeman, Donald (McGraw -Hill, 2005)
ICON has been developed as a result of an in-depth research project into the role of the course book in effective teaching and learning. From this research, the series has distilled a set of core activities, which are varied and recurring to create effective teacher-learner interaction in the classroom. ICON has been designed to support students and teachers in both large and small classes.